PARTISIPASI MASYARAKAT TERHADAP PROGRAM PENGELOLAAN TEKNOLOGI TERPADU BERBASIS MASYARAKAT DI KAWASAN DAERAH ALIRAN SUNGAI (DAS) SIAK RW.02 KELURAHAN SRI MERANTI KECAMATAN RUMBAI KOTA PEKANBARU 2015-2016 - Audina Reihan; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Most of the slums in the city of Pekanbaru are areas located around the Siak river. In addition to slum areas, river basins mostly have problems related to healthy lifestyles because most of the people who live in watershed areas use river water for daily life. The siak river flows have been polluted with rubber mill waste so the river water which is the source of life is not suitable for daily life. As the result, the community is not growing and not prosperous. In terms of formulating development strategies to improve the welfare of the community, it is necessary to pay attention to the general conditions and potentials of the said region. In addition, also considered the main issues and obstacles that exist in the community. One of the factors that affect the welfare of the community is the declining of the slum area, the number of poverty and the decrease in the number of unemployed. The Community Based Integrated Technology Processing Program in Siak Watershed Area is one of the government's ways to empower the people who live along the Siak river, namely RW 02 of Sri Meranti Sub-district, Rumbai District. With this program, it is hoped that the community can change the unhygienic lifestyles by no longer constructing the MCK (toilet, bath, and wash) along the river stream, consuming clean water and inviting the community to do the same as running the government program as a joint effort.In this case community participation is needed to achieve the goal of the establishment of Community-Based Integrated Technology Processing Program in Siak Watershed Area. However, after a year there has been no change in society due to lack of community participation in the program. People are still reluctant to consume clean water that has been distilled and still using the public bathroom on the edge of the river for daily needs and polluted the river water. In addition, thereJOM FISIP Vol. 4 No. 2 – Oktober 2017 Page 2are obstacles in running the existing program so that the Community Based Integrated Technology Processing Program in the Siak Watershed Area is not on target.The research method used in this research is descriptive research, with quantitative approach supported by qualitative where the author distributed questionnaires to the respondents and interviewed a number of figures as well as direct observation in the field to get a picture directly about the real condition that there is happening in community and installation buildings.The result of the research shows that in general, the participation of RW 02 community of Sri Meranti Sub-district, Rumbai District in the implementation of Community Based Integrated Technology Processing Program in Siak Watershed Area is not doing so well. There are factors that become obstacles of participation from RW 02 community of Sri Meranti Sub-district, Rumbai District such as community's mindset influenced by education level and public income, and lack of government supervision.Keywords: community, community participation, watershed area, Sri Meranti.